Service quality impact on customer degree of satisfaction in the context of international supply chain department at DHL Global Forwarding (Bangladesh) Ltd. - Dhar, Showmik (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.